Relationship Between Gender, Age, Duration And Frequency Of Hemodialysis Therapy With The Creatinine Level reduction Of Pre And Post Hemodialysis - Anny Thuraidah; Misbawati Misbawati; Nurlailah Nurlailah; Haitami Haitami (Medical Laboratory Technology Journal, 2019)
The kidneys are organs of the body that function to regulate water balance in the body, the concentration of electrolytes in the blood and acid-base balance and secretion of waste material. If the kidney fails to function, the patient will need immediate treatment and even undergo hemodialysis (HD) therapy. A critical indicator in determining whether a person with impaired kidney function requires HD therapy is to know the creatinine level. The study aimed to ascertain the differences in creatinine levels pre and post HD also study the relationship between the age, gender, duration and frequency of HD therapy of respondents with the decrease of creatinine levels pre and post. Type of research detailed survey with a cross-sectional design. The sample was taken using a total sampling technique of 35 respondents from H BadaruddinKasimHospitalin Tanjung with a sample examination technique using the Jaffe method. The examination results of creatinine levels average for pre and post hemodialysis was11,36 and 5,58 mg/dl, which decreased 51%. The analysis statistically used Paired T-Test has a p-value = 0,000, indicating a significant difference for creatinine levels pre and post HD. Relationship between Age, Gender, Duration, and Frequency of HD Therapy with the decrease of creatinine levels pre and post HD was analyzed with Spearmen correlation and had p values more than 0,05. It means there was no relation between them. Conclusion there were significant differences in creatinine levels reduction pre and post HD while the relationship between the four of respondent characteristics to the magnitude of creatinine reduction show that there was no significant relationship.